Pengaruh E-Wom Terhadap Green Purchase Intention: Peran Mediator pada Produk Kosmetik di Kota Batam - Randy Randy; Lily Purwianti; Listia Nurjanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyzes the effect of Electronic Word of Mouth (E-WOM) on Green Purchase Intention (GPI) by examining the mediating roles of Attitude, Environmental Concern, Health Concern, Perceived Behavioral Control, and Subjective Norm. This study is a quantitative study using a purposive sampling method with a population of 352 green product users in Batam City. Data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results indicate that all variables have a significant influence on GPI, where E-WOM directly strengthens attitudes, environmental awareness, health concern, subjective norms, and perceived behavioral control. The indirect effect analysis shows that Environmental Concern, Health Concern, Perceived Behavioral Control, and Subjective Norm significantly mediate the relationship between E-WOM and GPI, whereas Attitude does not serve as a significant mediator. These findings reveal that digital information shared through social media plays a vital role in shaping ecological awareness and consumer confidence in purchasing green products. The study extends the Theory of Planned Behavior by incorporating health and environmental dimensions as cognitive–affective mediators. Practically, the findings highlight the importance of digital communication strategies that emphasize health benefits, ecological value, and ease of access to strengthen consumers’ intention to purchase green products in Indonesia